Building National Identity: "Antígona Vélez" - Ristorto, Marcela Alejandra; Reyes, Silvia Susana (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
The purpose of this paper is to reflect upon Leopoldo Marechal's recreating Sophocles' Antigone in his Antígona Vélez. In the Greek tragegy, the contrast between Creon and Antigone implies political and religious issues of greater importance. It is a simplistic perspective to state that the play presents a contrast between a religious viewpoint (Antigone) and a political one (Creon). Rather, in Antigone's act of defiance of the city (polis), it is necessary to recognise a political as well as a religious action, and that Creon's exposure of Polyneices' body arises from political and religious convictions as well. In other words, the tragedy expresses the historical contradiction between noble families and the city. Thus, opposite religious and political attitudes correspond: Creon is the defender of the city and of its gods; Antigone, the defender of family and of the gods invoked in a funeral, the ceremony underlying family union and its exclusivity. This tension is historically explained: strong and indissoluble blood ties have existed from time immemorial, since noble families, much older than the city itself, even in the democratic Athens of the fifth century B.C., showed evident signs of power as rivals and also presented a potential threat against the latest institutions of the city. Thebes becomes, for the Argentine author, an hacienda, “La Postrera”, situated on the border dividing “civilization” from indigenous barbarism. And the confrontation between Antígona and Facundo Galván serves as a background to the civilization-barbarism opposition, expressed in terms of a “combat formula”, as a call for exclusion and extermination of the other. It could be asserted that Marechal's recreating must be placed on the debate upon defining national identity from the dichotomy civilization / barbarism.